Sistema de control automático de pasteurización - Elizondo-Ramírez, Diego Humberto (Instituto Tecnológico de Costa Rica, 2015)
Recently, the demand for natural products has increased, this leads to companies to develop and have more efficient processes; which is achieved through progressive automation of the crucial elements of production. In the case of the sponsoring company's project was begun by the process of pasteurization, one of which must be carried out with greater precision and speed. Automated pasteurization and is used by most developed dairy companies, but the challenge was to do it with the lowest possible cost; this meant not only to find the cheapest components that met the requirements, in addition to reuse the materials, components and existing devices, adapting to the new system. However, in order to adapt to an electronic system mechanical elements had to make several changes; as replacing devices with temperature measurement thermocouples compatible with the existing pipe connections. Also, take the motor starters and instead of a button, using the activation of a coil, which by means of an electric drive and an interlock, keep feeding pumps until the end of the process or disable an operator by a risk. Subsequently, a measurement system in real time is developed by an HMI display and storage of data in an external memory; for further review of the process and records required by the companies responsible for selling the product, performing regular audits. Finally, it allowed provided inputs and outputs for the other sections of the production process in order to automate it completely in the near future, goal set at the beginning by the owner; however because of time it will be left for later stages.
Proyecto de Graduación (Licenciatura en Ingeniería en Mecatrónica) Instituto Tecnológico de Costa Rica, Área Académica de Ingeniería en Mecatrónica, 2015.
Keywords: Automatización; Demanda; Eficiencia; Precisión